Causal Relationship Model of Quality Thai Nursing Education: Research Synthesis Using Meta–Analytic Structural Equation Modeling (MASEM) - Kulprateepunya, Kunthida; Vongprasert, Jumlong; Ruengtrakul, Auyporn (Journal of Health Science of Thailand, 2017)
The objectives of this study were to analyze effect size of nursing students characteristics, nurse instructors characteristics, administrators characteristics, curriculum characteristics, learning process, organization process, material support, cooperation between nursing education department and service department, and professional organization; and to develop causal relationship model of quality Thai nursing education. The samples were 138 research studies published during 1999 - 2012 derived from 39 universities and organizations. Quantitative data were analyzed using meta-analysis and the model was validated and test using structural equation modeling by M-Plus. The results of the study were as following: (1) the effect size of nursing students characteristics, nurse instructors characteristics, administrators characteristics, nurse instructors characteristics, learning process, organization process, material support, cooperation between nursing education department and service department, and professional organization affected to quality of nursing education were 0.410, 0.330, 0.408, 0.668, 0.438, 0.445, 0.228, 0.519 and 0.909 respectively; (2) the proposed model fit with the empirical data (χ2 = 368.604, df = 327, p = 0.056, CFI = 0.997, TLI = 0.996, RMSEA = 0.020) and predicted quality of Thai nursing education about 71.6 percents. Material support, organized administration, co-operation between nursing education department and service setting, respectively, had the strongest indirect effects. Recommendations from the study show to adjust the factors of curriculum characteristics could be changed learning process that effect to quality of Thai nursing education.